1990
DOI: 10.1073/pnas.87.2.701
|View full text |Cite
|
Sign up to set email alerts
|

Localizing multiple X chromosome-linked retinitis pigmentosa loci using multilocus homogeneity tests.

Abstract: Multilocus linkage analysis of 62 family pedigrees with X chromosome-linked retinitis pigmentosa (XLRP) was undertaken to determine the presence of possible multiple disease loci and to reliably estimate their map location. Multilocus homogeneity tests furnished convincing evidence for the presence of two XLRP loci, the likelihood ratio being 6.4 x 109:1 in favor of two versus a single XLRP locus and gave accurate estimates for their map location. In 60-75% of the families, location of an XLRP gene was estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
91
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(92 citation statements)
references
References 10 publications
0
91
0
1
Order By: Relevance
“…As in any polygenic disease, no single gene is sufficient or, in general, necessary to cause the disease; therefore, although linkage with the HLA region has been detected in most IgAD patients and in all instances the risk attributable to this region is roughly equal, this does not indicate that just one MHC gene is conferring susceptibility to all of them. Functionally related genes are frequently linked to each other (38) and a single linkage signal to a region of a chromosome may actually be the result of disease-predisposing alleles in different linked genes in different pedigrees, as is the case for X-linked retinitis pigmentosa, where the existence of several genetic defects in the same chromosomal region has been proven (39). The MHC (HLA region in humans) is an extended cluster of genes that are remarkable for the number and importance of the immunological functions they encode (40,41), and already, in some other immune-mediated diseases, more than one MHC gene has been primarily involved (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…As in any polygenic disease, no single gene is sufficient or, in general, necessary to cause the disease; therefore, although linkage with the HLA region has been detected in most IgAD patients and in all instances the risk attributable to this region is roughly equal, this does not indicate that just one MHC gene is conferring susceptibility to all of them. Functionally related genes are frequently linked to each other (38) and a single linkage signal to a region of a chromosome may actually be the result of disease-predisposing alleles in different linked genes in different pedigrees, as is the case for X-linked retinitis pigmentosa, where the existence of several genetic defects in the same chromosomal region has been proven (39). The MHC (HLA region in humans) is an extended cluster of genes that are remarkable for the number and importance of the immunological functions they encode (40,41), and already, in some other immune-mediated diseases, more than one MHC gene has been primarily involved (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Close linkage of XLRP to markers DXS7 [Bhattacharya et al, 1984;Nussbaum et al, 1985] and OTC [Musarella et al, 1988;Chen et al, 1988;Denton et al, 1988;Wirth et al, 1988;Musarella et al, 1989] was found. Subsequent linkage analysis provided evidence for two different loci: RP2 (MIM# 312600) was positioned centromeric of DXS7, while RP3 (MIM# 312610) was telomeric of DXS7 and mapped between DXS1110 and OTC [Musarella et al, 1988;Chen et al, 1989;Musarella et al, 1990;Ott et al, 1990;Dahl et al, 1991]. On the basis of linkage analyses, the frequency of RP3 as a fraction of XLRP is 56 to 90%, and RP2 accounts for most of the remainder Ott et al, 1990;Teague et al, 1994;Bergen et al, 1995;Fujita et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent linkage analysis provided evidence for two different loci: RP2 (MIM# 312600) was positioned centromeric of DXS7, while RP3 (MIM# 312610) was telomeric of DXS7 and mapped between DXS1110 and OTC [Musarella et al, 1988;Chen et al, 1989;Musarella et al, 1990;Ott et al, 1990;Dahl et al, 1991]. On the basis of linkage analyses, the frequency of RP3 as a fraction of XLRP is 56 to 90%, and RP2 accounts for most of the remainder Ott et al, 1990;Teague et al, 1994;Bergen et al, 1995;Fujita et al, 1997]. Cloning of RP2 in Xp11.23 [Schwahn et al, 1998] (MIM# 312600) and subsequent mutation analysis have confirmed that RP2 accounts for 10 to 25% of XLRP.…”
Section: Introductionmentioning
confidence: 99%
“…XLRP has been genetically mapped to at least five loci: RP2, RP3, RP23, RP24, and RP34 [Meindl et al, 1996;Gieser et al, 1998;Schwahn et al, 1998;Hardcastle et al, 2000;Melamud et al, 2006]. RP3 is predicted to account for 70 to 90% of XLRP cases [Ott et al, 1990;Teague et al, 1994], the RP GTPase regulator (RPGR) gene (MIM] 312610) accounts for the RP3 locus and is mutated in up to 20% of all RP patients [Breuer et al, 2002].…”
Section: Introductionmentioning
confidence: 99%